Strokovna samozavest pri spodbujanju bralne pismenosti - Fras Popović, Sabina (Organizacija znanja, 2021)
Participation in professional events in the fields of reading literacy and reading culture has a positive impact on boosting professional self-confidence. The available data reflects the accessibility of professional events for the promotion of reading literacy and reading culture in Slovenia. Practitioners attend such training, but at the same time, they doubt their competence to encourage and plan the development of reading literacy and reading culture. This study uses research methodology of 1) a review of publicly available data and published research, and 2) case study, with survey method. The question about the participants' feelings when transferring a professional event from a physical to an online environment has been added to the main research question. The research shows that professional events have a significant impact on professional self-confidence, on understanding one's role and her/his contribution to the reading literacy promotion, and thus, they shape one's attitude towards reading and books. In terms of participants' feelings when watching events online, satisfaction with socialising with colleagues and with the event venue is replaced by satisfaction with the content provided. The case study is based on an event organised by the Centre for Reading Literacy Promotion at the Maribor Public Library.
Keywords: bralna kultura; bralna pismenost; impact; professional events; professional self-confidence; reading culture; reading literacy; strokovna samozavest; strokovni dogodki; vpliv